2011
DOI: 10.1016/j.fertnstert.2011.02.052
|View full text |Cite
|
Sign up to set email alerts
|

Semen quality analysis of military personnel from six geographical areas of the People’s Republic of China

Abstract: Capsule:This is the first attempt in China to examine the determinants of semen quality by investigating a large sample of military servicemen from different geographical areas. Lower semen parameters were found and potential influences were putatively identified. Result(s):The median valuess were 3.0 ml for semen volume, 39. absabstinence all duration were found to be significantly associated with semen quality (Pp<0.001). Conclusion(s):The subjects had markedly lower mean sperm concentrations, sperm counts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 37 publications
3
25
0
4
Order By: Relevance
“…During the past decades there has been much discussion about changes in semen quality with some studies finding significant declines (Carlsen et al, 1992;Auger et al, 1995;Irvine et al, 1996;Zou et al, 2011) and others finding no change (Bujan et al, 1996;Fisch et al, 1996;Paulsen et al, 1996). Despite the heterogeneity in study populations, overall, the data support a decline in sperm concentration in most Western countries (Swan et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…During the past decades there has been much discussion about changes in semen quality with some studies finding significant declines (Carlsen et al, 1992;Auger et al, 1995;Irvine et al, 1996;Zou et al, 2011) and others finding no change (Bujan et al, 1996;Fisch et al, 1996;Paulsen et al, 1996). Despite the heterogeneity in study populations, overall, the data support a decline in sperm concentration in most Western countries (Swan et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Although there may appear to be ethnic differences, they may actually be geographic or regional differences. This has been noted in the United States, 122,123 Europe, 124 France, 125 China, 126,127 and Japan. 128 These regional differences may include ethnic differences, but also social economic status, lifestyle, climate, and other regional exposures such as pesticides, air pollution, etc.…”
Section: Questions From the Panel Q1mentioning
confidence: 76%
“…For example, the sperm concentration in the Chongqing area of southwest China was significantly low in summer (June) 25 ; on the other hand, military personnel from the People's Republic of China displayed significantly low values in autumn (September, October). 26 These differences might have been due to demographic characteristics, lifestyle factors, environmental factors or genetic variation; however, this needs to be clarified in future. In the present study, we showed that the sperm concentrations in January and June differ within Y chromosome haplogroups.…”
Section: Resultsmentioning
confidence: 99%